2001
DOI: 10.1002/1615-4169(200108)343:6/7<591::aid-adsc591>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity and Regioselectivity of Tryptophan 7-Halogenase fromPseudomonas fluorescensBL915

Abstract: Tryptophan 7‐halogenase which is involved in pyrrolnitrin biosynthesis is the first halogenating enzyme to be isolated that has substrate specificity and regioselectivity. This FADH2‐dependent halogenase catalyzes the chlorination of its natural substrate tryptophan exclusively at the 7‐position, a position at which direct chemical chlorination is not possible. Other substrates such as N‐Ω‐methyltryptamine, 5‐methyltryptamine, 5‐methylindole, 3‐methylindole, or indole‐3‐acetonitrile are also chlorinated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 0 publications
0
35
1
2
Order By: Relevance
“…Despite the many representatives of this halogenase class and its role in the biosynthesis of medicinally important halogenated aromatic natural products, only a few of these catalysts have been characterized (9)(10)(11). PrnA, the Trp-7-halogenase involved in the formation of pyrrolnitrin, is foremost among FADH 2 -dependent halogenases that have been described (9,10).…”
mentioning
confidence: 99%
“…Despite the many representatives of this halogenase class and its role in the biosynthesis of medicinally important halogenated aromatic natural products, only a few of these catalysts have been characterized (9)(10)(11). PrnA, the Trp-7-halogenase involved in the formation of pyrrolnitrin, is foremost among FADH 2 -dependent halogenases that have been described (9,10).…”
mentioning
confidence: 99%
“…The large structural differences between these substrates and 2-amino Several notable differences between the reactivity RebH and that reported for PrnA deserve comment given the significant homology of both the complete sequences (55%) and the active sites (vide infra) of these two enzymes. First, PrnA was reported to have no activity on indole, gramine, or 1-methyl-L-tryptophan, [11] whereas RebH halogenated each of these substrates. The simplest explanation for this difference is that low conversion using PrnA precluded identification of the halogenated products.…”
Section: Nih Public Accessmentioning
confidence: 85%
“…[14] As part of one such effort, O'Connor and coworkers demonstrated that tryptamine is accepted by RebH and is halogenated at the 7-position, [15] which contrasts with the preference for halogenation of the 2-position of this substrate by PrnA. [11] Inspired by these examples, we set out to explore the synthetic utility of RebH in preparative halogenation reactions. We focused on this enzyme and its cognate flavin reductase, RebF, due to reports of their expression in E. coli, [13] which facilitates both enzyme production and genetic manipulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations